PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN OBYEK WISATA THE LAWU FRESH DI DESA PUNTUKREJO, KECAMATAN NGARGOYOSO, KABUPATEN KARANGANYAR - Anwar Sulthani, Alrizal; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2024)
The Lawu Fresh tourist destination in Puntukrejo Village has the potential to be developed into a prominent tourist destination. Empowering the local community is seen as a crucial step in this development. Identifying the empowerment process that can optimize the development of The Lawu Fresh tourist attraction is necessary. The aim of this research is to identify the community empowerment process in developing The Lawu Fresh tourist attraction, along with factors that support or hinder this empowerment process. This study employs a qualitative descriptive research method. The findings indicate that the empowerment process is underway but not yet fully optimized. In the awareness-raising stage, some community members are reluctant to participate in empowerment activities, while in the capacity-building stage, there are constraints due to limited resources. Supporting factors include the welfare dimension, where community empowerment activities can enhance economic conditions and bring positive impacts to society; the access dimension, through availability of facilities supporting empowerment activities; and the control dimension, involving community involvement in management and equitable utilization. Hindering factors include the critical awareness dimension, where community consistency in participating in empowerment activities is lacking, and the participation dimension, constrained by budget limitations. Recommendations include intensifying community engagement through discussions on the benefits of empowerment and efficiently planning budgets while seeking external sponsors or investors.